2017
DOI: 10.1159/000484604
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of FGFR2 in Fibroblasts Ameliorates Kidney Fibrosis after Ischemia/Reperfusion Injury in Mice

Abstract: Background: Fibroblast growth factors (FGFs) are heparin-binding proteins involved in a variety of biological processes. However, the role and mechanisms of FGF/FGFR2 signaling in fibroblast activation and kidney fibrosis need further investigation. Methods: In this study, a mouse model with fibroblast-specific FGFR2 gene disruption was generated. The knockouts were born normal and no kidney dysfunction or histological abnormality was found within 2 months after birth. A kidney ischemia/reperfusion injury (IRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…SMAD1 is a protein mediating TGF-b signalling, activated by α-SMA, that was delineated to be elevated in the skin of patients with SSc i liver fibrosis 56 . FGF2 and FGFR2 are profibrogenic factors that may support the proliferation and activation of kidney fibroblasts, which contribute to the development of renal fibrosis 57 . FOXO3 is an important integrator of profibrotic signaling in lung fibrosis and was found to be downregulated in IPF myofibroblasts 58 .…”
Section: Resultsmentioning
confidence: 99%
“…SMAD1 is a protein mediating TGF-b signalling, activated by α-SMA, that was delineated to be elevated in the skin of patients with SSc i liver fibrosis 56 . FGF2 and FGFR2 are profibrogenic factors that may support the proliferation and activation of kidney fibroblasts, which contribute to the development of renal fibrosis 57 . FOXO3 is an important integrator of profibrotic signaling in lung fibrosis and was found to be downregulated in IPF myofibroblasts 58 .…”
Section: Resultsmentioning
confidence: 99%
“…It was found that bFGF facilitates epithelial-to-mesenchymal transition of tubular epithelial cells [ 55 ]. Mice with fibroblast-specific disruption of the FGFR2 gene demonstrated decreased total collagen deposition, fibronectin, and alpha smooth muscle actin expression in an ischemia-reperfusion model [ 56 , 57 ]. On the other hand, treatment with bFGF alleviated oxidative stress and apoptosis in the kidney in db / db mice [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…FGF2 reduces the expression of renal damage markers such as ED-1 and a-smooth muscle actin and participates in the regeneration process after ischemic acute renal failure (Villanueva et al, 2006). Xu et al revealed the same results upon the ablation of the receptor FGFR2 in fibroblasts (Xu and Dai, 2017). Such genetic manipulation ameliorates kidney fibrosis after IRI in mice.…”
mentioning
confidence: 88%
“…Although IRI mainly affects renal tubular cells, IR-induced pathogenic process and its repair involve interactions between interstitial cells, infiltrated inflammatory cells and epithelial cells. Interestingly, a recent study using a mouse model with fibroblastspecific ablation of Fgfr2 gene indicated that FGFR2 expression in fibroblast may contribute to kidney fibrosis after IRI through promoting renal fibroblast activation and proliferation (Xu and Dai, 2017).…”
Section: Fgfrs Involved In Akimentioning
confidence: 99%
See 1 more Smart Citation